(untitled) (Scientific journal of the Fergana State University, 2024)
In this research work, based on the chemical composition of the above-ground parts of the leaves of the ruach plant growing in Namangan region and the above-ground parts of jusai plants growing in Fergana province in a ratio of 3:1 (consisting of 75% ruach and 25% jusai) obtained As Rheum food additive was studied by high-performance liquid chromatography method.